From Marx to Gramsci to us: Laboratory to prison, and back - Beilharz, Peter (Sage, 2016)
Marx and Gramsci remain two of the most constant presences and inspirations for those on the left. Yet there is a persistent sense that we have still to get them right. Perhaps this indicates that sources like this are now fully classics, to be returned, and returned to. In the case of Marx and Gramsci, a series of major works published in the Brill Historical Materialism series breaks new ground as well as returning to older controversies, both resolved and unresolved. Apart from remaining arguments concerning the status of materials unpublished in their own lifetimes, the major tension that emerges here is that between the task of immanent, contextual philology and the challenge of reading ‘Marx for today’ or ‘Gramsci for today’. The tension between text and context, and the question of what travels, conceptually persists.